Challenges Nigerian Journalists Face in Spotting Fake News - Okocha, Desmond Onyemechi; James, Akpandem Friday (Universitas Negeri Surabaya, 2025)
Historically, Nigerian journalism has contended with socio-political pressures, economic constraints and regulatory threats, but the advent of fake news in the digital age has further complicated the media landscape. This study explored the perspectives of Nigerian journalists on fake news, examining their understanding of its impact, the challenges they encounter in spotting false narratives and the motivations driving the spread. Anchored on Agenda-Setting Theory and supported by the Technology Determinism Theory, the research highlighted how technological advancements have facilitated journalistic practices and allowed misinformation to thrive. Using a quantitative research method, questionnaire was administered to 200 practicing journalists across the six geopolitical regions of the country. Key findings indicate that fake news is widespread, with social media identified as a major driver. Journalists reported a lack of adequate training in verification practices. Existing fact-checking protocols were found to require reinforcement. The study underscored the need for adherence to ethical standards, enhanced media literacy among professionals and the public, collaboration among stakeholders and investment in tools and training to tackle fake news effectively. It recommends a balanced regulation that ensures accountability while safeguarding freedom of expression. Addressing these challenges comprehensively, Nigerian journalism can strengthen its role as a credible source of information and restore public trust in media reporting